Web-Based E-Module with a Project Based Learning Approach to Improve Computational Thinking Skills of High School Students - Yohanes Parsaoran Selano; Leo Agung Sutimin; Sri Sumaryati (Journal of Education Technology)
Technology integration in education faces significant challenges, including the limited use of interactive learning media. This study addresses these challenges, so the purpose of this study is to develop a website-based e-module integrated with the Project-Based Learning (PjBL) approach to improve computational thinking skills in high school programming education. This type of research is developed with the Borg & Gall model, which is simplified into three stages (planning, development, and testing). This study involved media experts, content experts, practitioners, and students as research subjects. Data was collected through observation and questionnaires, while the product's effectiveness was analyzed using N-Gain score analysis. The research findings revealed that the limited variety of learning media used by IT teachers reduced students' enthusiasm and hindered their computational thinking development. In response, a website-based e-module was designed and validated during development. Feedback from media experts, content experts, teachers, and students during individual and small group testing indicated a "very good" qualification for product feasibility. The test results showed that the e-module significantly improved students' computational thinking skills, with an increase in scores from 73.6 (pre-test) to 97.3 (post-test), which is categorized as "high" in the N-Gain score analysis. These results confirm that the website-based e-module with the PjBL approach is very effective and suitable for addressing the challenges of programming education and fostering computational thinking skills in high school students. The study implies that the website-based module with the PjBL approach can be used in learning.